PENGARUH FREKUENSI PEMBILASAN FILTER ARANG AKTIF BATOK KELAPA DAN SPONS PADA SISTEM RESIRKULASI TERHADAP KUALITAS AIR MEDIA PEMELIHARAAN IKAN MAANVIS (Pterophyllum Scalare) - Dedi . Apriadi; Dade . Jubaedah; Marini . Wijayanti (Jurnal Akuakultur Rawa Indonesia, 2017)
ABSTRACTThe frequency of flushing on coconut charcoal and sponge filters by Recirculation Aquaculture System (RAS) can apply to maintain water quality. This research was conducted on Laboratorium Dasar Perikanan, Department of Aquaculture, Faculty of Agriculture, Sriwijaya University from March to May 2017. The study used Completely Randomized Design with 4 treatments and 3 replications. The treatment were using filter flushing every week (P1), 2 weeks (P2), 3 weeks (P3) and without leaching (P4). The parameters observed were temperature, pH, dissolved oxygen (DO), turbidity, total dissolved solids (TDS) and ammonia. The results showed that the flushingfrequency gave of the filter has a positive effect on water quality parameters. Treatment P2 has resulting better water quality such as temperature (28.3-29.2), pH (6.9-7.2), DO (1.11 mg.L-1), Turbidity (0.00 NTU), TDS (22.33 mg.L-1), ammonia (0.020 mg.L-1), survival rate 83.33%, absolute growth (0.93 cm for lenght and 0.58 g for weight). Keywords: flushing of filter, resirculation system, water quality, angelfish